Economic Integration, Monopoly Power and Productivity Growth without Scale Effects. Issue 1 (February 2016) - Davis, Colin; Hashimoto, Ken‐ichi
Abstract: This paper considers how monopoly power affects the relationship between economic integration and economic growth that is not biased by a scale effect. In a two‐country model of trade, productivity growth is generated by firm‐level investment in process innovation, and the location of economic activity is determined by relative market size, trade costs and imperfect knowledge diffusion. Equilibrium features the partial concentration of manufacturing and the full concentration of innovation in the larger country. Increased economic integration raises the concentration of manufacturing in the larger country, and when monopoly power is strong, leads to decreased product variety, accelerated productivity growth and greater national welfare. With weak monopoly power, however, it raises product variety and dampens productivity growth, but may benefit or hurt welfare.